A comparative analysis of the representation of gender equality Awareness in Lucy, The Woman Warrior and The God of Small Things novels - Simamora, Rosa Maria; Tarigan, Karisma Erikson; Simanihuruk, Bertova; Gurning, Bonar; Lariesto, Pioro Benevolent; Yusuf, Muhammad (Research Journal in Advanced Humanities, 2025)
This research aims at exploring gender equality represented in three novels namely Lucy, The Woman Warrior and The God Small Things Novels. This study employed qualitative and quantitative approach. This study applied feminist literary criticism and pragmatic theories. Questioners were addressed to 48 women students of Department of English Literature, Universitas Katolik Santo Thomas who have read the novels to see if they are empowered. From the analysis, it can be concluded that those the three novels empower women to be more aware of gender equality specially fighting for rights, freedom and opportunities. By appreciating, the novels, the women/students understand and measure their self-potential to develop, understand the norms and customs and how to respond, and underline that education is one of the most crucial things to enhance self-values through studying hard, finishing study on time, and finding jobs. From 48 women students who are addressed the questioners, 47 corresponds give yes answers. It means that the novels empower them to be aware of gender equality.